Sustainability, safety, and applications of nanomaterials-based corrosion inhibitors - Kumar, Ashish; Thakur, Abhinay (IGI Global, 2024)
In an era defined by the imperatives of sustainability and technological innovation, the quest for effective corrosion prevention solutions has assumed unprecedented significance. Against the backdrop of global challenges such as climate change, aging infrastructure, and resource depletion, nanomaterials-based corrosion inhibitors offer a promising pathway towards enhancing the durability, safety, and environmental sustainability of critical systems.Sustainability, Safety, and Applications of Nanomaterials-Based Corrosion Inhibitors contextualizes the relevance of nanotechnology in addressing these pressing concerns, highlighting its role in advancing sustainable development goals and fostering resilience in the face of corrosion-related challenges. It discusses how nanotechnology can revolutionize corrosion inhibition strategies for the sustainable development of infrastructure in the 21st century. Covering topics such as coating techniques, space exploration, and aerospace engineering, this book is a useful resource for engineers, scientists, researchers, industry professionals, business owners, and academicians.